La méthode de la photo-interview à partir de la photographie aérienne - Laetitia Delavoipière; Sylvaine Conord; Anaïs Marshall (EchoGéo)
Aerial photography presents almost exhaustively the morphology and land use of the photographed space, but does not represent the social dimension of the studied territory. This article mentions an example of a particular use of the photo-interview method introducing pictures during interviews so that they become a vector for discussions and exchanges. Adapted to aerial photography, this investigative technique was tested with two former residents of a slum in Nanterre. The collection of reactions to the images of the spaces they had lived has enriched the territorial analysis in a research work on the precarious urbanization of Nanterre.